Columnar cell variant of papillary thyroid carcinoma: Cytomorphological characteristics of 11 cases with histological correlation and literature review. Issue 6 (3rd April 2017) - Bongiovanni, Massimo; Mermod, Maxime; Canberk, Sule; Saglietti, Chiara; Sykiotis, Gerasimos P.; Pusztaszeri, Marc; Ragazzi, Moira; Mazzucchelli, Luca; Giovanella, Luca; Piana, Simonetta
Abstract : BACKGROUND: The columnar cell variant of papillary thyroid carcinoma (PTC‐CCV) is a rare entity that demonstrates a more aggressive clinical course compared with the more common subtypes of PTC. On histology, it is defined by papillae or gland‐like structures lined by columnar cells displaying prominent nuclear stratification. Because to the authors' knowledge no characteristic cytomorphological features have been identified to date and typical features of PTC often are absent on cytology, the diagnosis of PTC‐CCV by fine‐needle aspiration (FNA) is challenging. This prompted the authors to evaluate a series of PTC‐CCV cases to identify features that could facilitate its diagnosis by FNA. METHODS: A total of 11 surgical specimens of PTC‐CCV with corresponding preoperative cytology were identified over a 21‐year period. The cytological features of the aspirated specimens, consisting mostly of Papanicolaou and Diff‐Quick smears, were evaluated retrospectively. RESULTS: All cases demonstrated the presence of papillary structures. The most important features observed in PTC‐CCV FNA specimens were hypercellularity with nuclear superposition and a paucity of nuclear pseudoinclusions and grooves. CONCLUSIONS: Although PTC‐CCV may demonstrate features that overlap with those of the classic variant of PTC, hypercellular smears with papillary structures covered by cells with pseudostratified nuclei that show a paucity of nuclear pseudoinclusions and grooves should alert the cytopathologist to the possibility of this diagnosis. Cancer Cytopathol 2017;125:389–97 . © 2017 American Cancer Society . Abstract : The columnar cell variant of papillary thyroid carcinoma is a rare and poorly described subtype, the diagnosis of which often is missed on fine‐needle aspiration cytology. Its distinguishing cytomorphological features are hypercellular smears with papillary structures covered by cells with pseudostratified nuclei and a paucity of nuclear pseudoinclusions and nuclear grooves.